HUBUNGAN PERSEPSI PADA GAYA KEPEMIMPINAN ATASAN DENGAN MOTIVASI KERJA PEGAWAI DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KOTA BINJAI - Meliala, Sinarsi; Nursiti, Dwi; Ramadhani, Sri; Putri, Selvi Untari (JURNAL PSYCHOMUTIARA, 2022)
Nowadays employee work motivation is one topic that is always interesting and considered important, both by scientists and practitioners, precisely because work motivation is seen as influencing the running of the organization as a whole. Leaders have a role in advancing the company or organization. This study aims to determine the relationship between perceptions of superior leadership style and work motivation, where the subjects in this study are employees of the Housing and Settlement Service of Binjai City, with a total of 40 employees. The sampling technique used the total sampling technique (census). The data collection method in this study uses a Likert scale. The data analysis method used is Product Moment Correlation. The results of this study indicate that the perception of a superior leadership style has a delegating style of leadership. Work motivation of 32.5% employees who have high, and 12.5% low and 55% medium. The results of the correlation test are significant values 0.620> 0.05, which means that there is a relationship between perceptual variables on superior leadership style and work motivation variables. This result answers the research hypothesis that there is a relationship between perceptions of superior leadership style and work motivation of the employees of the Housing and Settlement Service of Binjai City, so Ha is accepted and Ho is rejected.